Evaluating The Environmental Impacts of Electricity Grids and Geographical Factors on Co₂ Emissions from Electric Vehicle Adoption - Lucia Diawati; Fandi Rahanra (Jurnal Teknologi dan Manajemen Industri Terapan, 2024)
The global interest in electric vehicles (EVs) to reduce CO2 emissions requires understanding their emission-mitigating factors. This study investigates how electricity grid characteristics and geographical factors affect EV adoption and associated emissions. We address two questions: (1) Does a country's electricity grid significantly impact EV effectiveness in reducing CO2 emissions? and (2) To what extent does the geographical factor of EV production influence emissions? Two methodologies are used to answer these QRs: life cycle assessment to calculate the CO2 emission throughout the EV life cycle, subject to the electricity grid and EV supply chain, and system dynamics to simulate the impact of EV adoption on CO2 emission reduction. The results will provide valuable insights for policymakers, enabling them to design effective strategies to promote sustainable EV adoption and maximize the environmental benefits of transitioning to electric mobility.